A case report of lineage switch from T-cell acute leukemia to B-cell acute leukemia. Issue 44 (30th October 2020) - Zhu, Yejing; Liu, Hui; Zhang, Shuna; Liang, Yanyan; Xiao, Meng; Hao, Yunliang; Guan, Yun
Abstract: Rationale: ALL is the most common form of leukemia (75% to 80%), it is characterized by clonal expansion of the lymphoid blasts in bone marrow, blood, and other tissues, which can be divided into T lineage and B lineage. Although relapse of acute leukemia is common, a change of immunophenotype at relapse only occurs rarely. Some of these cases have been labeled "lineage switch". Patient concerns: A 31-year-old man had multiple lymph nodes in the neck, and the lymph nodes on the right side adhered to the surrounding tissues. His lymphocytes ratio in blood was up to 86.3%. Flow cytometry of the bone marrow aspirate showed positive results for CD2, CD5, CD7, cCD3, TDT, CD4, CD8, and CD10, negative results for CD34, CD117, CD33, HLA-DR, CD19, and CD20. Twenty six months later, the patient felt pain in the neck and shoulder after touching. His lymphocytes of blood were 109.9×109 /L. 43 fusion genes and positive BCR/ABL was detected. Flow cytometry of the bone marrow aspirate showed pro B lymphocytes accounted for 85.54%, and positive expression of CD38, CD10, CD34, CD33, TDT, CD9, and HLA-DR. Moreover, the RT-PCR data showed the patient expressed high level of T cell and B cell development transcription factors. Diagnoses: Upon examination, the patient was initially diagnosed with T-lineage pro cell ALL. BM morphologic analysis presented complete remission (CR) after systemic chemotherapy. Twenty six months later, we discovered the patient was diagnosed with B-lineage acute lymphocytic leukemia. Interventions: Systemic chemotherapy is first given when a patient was diagnosed with T-cell acute lymphoblastic leukemia. After the patient happened linage switch, we adjusted the treatment plan, and the patient was complete remission after 1 course of treatment. Outcomes: Our case provides information of lineage switch from T-ALL to B-ALL in this report, which is never seen in our knowledge. Lessons: This lineage switch from T-ALL to B-ALL is never reported beforemoreover, the RT-PCR data showed the patient expressed high level of T cell and B cell development transcription factors. Its early recognition can let doctor provides appropriate therapy to patient.